Angiogenesis in alkaptonuria. Issue 6 (26th September 2016) - Millucci, Lia; Bernardini, Giulia; Marzocchi, Barbara; Braconi, Daniela; Geminiani, Michela; Gambassi, Silvia; Laschi, Marcella; Frediani, Bruno; Galvagni, Federico; Orlandini, Maurizio; Santucci, Annalisa
Abstract: Alkaptonuria (AKU) is a rare genetic disease that affects the entire joint. Current standard of AKU treatment is palliative and little is known about its physiopathology. Neovascularization is involved in the pathogenesis of systemic inflammatory rheumatic diseases, a family of related disorders that includes AKU. Here, we investigated the presence of neoangiogenesis in AKU synovium and healthy controls. Synovium from AKU patients, who had undergone total joint replacement or arthroscopy, or from healthy patients without any history of rheumatic diseases, who underwent surgical operation following sport trauma was subjected to hematoxylin and eosin staining. Histologic grades were assigned for clinical disease activity and synovitis based on cellular content of the synovium. By immunofluorescence microscopy, using different endothelial cell markers, we observed large vascularization in AKU but not in healthy synovium. Moreover, Western blotting and quantification analyses confirmed strong expression of endothelial cell markers in AKU synovial tissues. Importantly, AKU synovium vascular endothelium expressed high levels of β‐dystroglycan, a protein previously involved in the regulation of angiogenesis in osteoarthritic synovium. This is the first report providing experimental evidences that new blood vessels are formed in AKU synovial tissues, opening new perspectives for AKU therapy.